THE IMPLEMENTATION OF AUDIO VISUAL IN TEACHING LISTENING : (An Experimental Study at SMK Negeri 3 Langsa) - Azizah (Getsempena English Education Journal, 2019)
This study was designed to discover the use of audio visual in teaching listening to the second year students of SMK Negeri 3 Langsa. The main goal of this study was to find out significant differences in students’ listening achievement taught by either audio visual or audiotape. Therefore, two classes were selected randomly as the samples from the targeted population. The first class using audio visual was an experimental group, while the second-class using audiotape was a control group. Each class consisted of 24 students provided data through pre-test and post-test. The scores of the tests were analyzed quantitatively. After examining the data collected from both groups, it was found that the mean score of the post-test of the experimental group (78,79) was higher than the mean score of the post-test of the control group (53,75). Moreover, both of scores were analyzed through ttest compared to ttable. The result of ttest was 8,44 and the result of ttable score at the level of significant degree α = 0,05 was 1,684. It displays that ttest score is higher than ttable (8,44 > 1,684). In other words, there is a significant difference in students’ listening achievement between the experimental and control groups. Thus, it can be taken into account that the alternative hypothesis is accepted, while the null hypothesis is rejected.